Pengaruh rasio likuiditas, rentabilitas dan aktivitas terhadap kinerja keuangan di RS Jiwa Dr. Radjiman Wediodiningrat Lawang - Fatoni, Achmad; Hidayati Rini, Nurul Sri (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
During a period of 8 years in Dr. Mental Hospital. Radjiman Wediodiningrat Lawang is suspected of having a decline in financial performance, so this research was conducted with the aim of analyzing liquidity ratios, profitability ratios and activity ratios simultaneously affecting financial performance. This type of scientific research uses a quantitative approach. The samples used are the ratio of Liquidity Ratio (current ratio), Profitability Ratio (ROA/Return On Assets), Activity Ratio (Collection Period) and Financial Performance (ROE/Return On equity) in 2014, 2015, 2016, 2017, 2018 , 2019, 2020 and 2021 which are in the BLU Financial Report of Dr. Mental Hospital. Radjiman Wediodiningrat Lawang The results showed that there is a significant influence of Liquidity Ratio on financial performance, Profitability Ratio on financial performance, Activity Ratio on financial performance and simultaneously the three ratios significantly affect financial performance.